ALGORITMA RANDOM PADA COMPUTER BASED TEST PENERIMAAN MAHASISWA BARU STTA YOGYAKARTA - Saiful Bahri; Hero Wintolo; Anton Setiawan Honggowibowo (Compiler, 2012)
The Admissions  in the College of Technology Adisutjipto Yogyakarta, the committee has had PMB Computer Based Test (CBT) to test new students since 2010. However, CBT is owned by STTA not support randomization and answer questions about each exam so issued, the order of questions and answers will remain the same. Of the many random algorithm, algorithm Congruential Linear Generators (LCG) is an algorithm suitable for use in scrambling about in CBT because of the rapid process of generating random numbers and the algorithm is easy to learn and implement. By giving feedback LCG a current value of the length of time it will produce a different value in each random from the first randomization. With randomness about the cheating in the exam PMB can be resolved.